Function of Mitochondrial Stat3 in Cellular Respiration - Wegrzyn, Joanna (2009)
Cytokines such as interleukin-6 induce tyrosine and serine phosphorylation of Stat3 that results in activation of Stat3-responsive genes. We provide evidence that Stat3 is present in the mitochondria of cultured cells and primary tissues, including the liver and heart. In Stat3(−/−) cells, the activities of complexes I and II of the electron transport chain (ETC) were significantly decreased. We identified Stat3 mutants that selectively restored the protein's function as a transcription factor or its functions within the ETC. In mice that do not express Stat3 in the heart, there were also selective defects in the activities of complexes I and II of the ETC. These data indicate that Stat3 is required for optimal function of the ETC, which may allow it to orchestrate responses to cellular homeostasis.